Good practices in milking to reduce microbiological contamination of milk in agreste of Pernambuco / Boas práticas de ordenha para redução da contaminação microbiológica do leite no agreste Pernambucano - Maria Beatriz Tassinari Ortolani; Ana Paula Pavão Battaglini; Alexandre Amorim Monteiro; Livia Cavaletti Corrêa da Silva; Rafael Fagnani; Ronaldo Tamanini; Vanerli Beloti; Marcelo Takeo Matsubara; Márcia de Aguiar Ferreira Barros (Semina: Ciências Agrárias, 2011)
In Pernambuco, as well as in the major part of Brazil, milk, especially in small dairy farms, is obtained in poor hygienic conditions, little technology and deficient sanitary control of animals. Raw milk presents low microbiologic quality, which compromises the product’s composition, reduces its shelf life and can constitute risk to public health. Food quality and safety are related to the Good Manufacturing Pratices (GMP). Implementation of GMP results in reduction of the number of microorganisms in milk, leading to a better microbiologic quality and enhanced shelf life of the final product. The aim of this work was to evaluate the impact of implementation of Good Milking Practices on the improvement of microbiological quality of milk, aiming to achieve the standards established by Normative Instruction 51. Different practices of milking were applied in the main points of contamination, identified previously, in four dairy farms of Agreste of Pernambuco. The practices were evaluated through enumeration of indicator microorganisms mesophilic aerobes, psychrotrophics, coagulase positive staphylococci, total coliforms and Escherichia coli before and after the application of the practices. The practices adopted were: elimination of first three jets of milk, immersion of teats in chlorinated solution, vigorous cleaning and posterior inversion of buckets and cans for elimination of residual water. Results showed, with the application of the practices, means reduction of 99.9% for mesophilic aerobes microorganisms. The practices indicated are simple, efficient, of easy adoption in milking routine in any situation of technology at the dairy farms and do not require spends with installations. Em Pernambuco, assim como na maior parte do país, o leite, sobretudo nas pequenas propriedades, é obtido em precárias condições higiênicas, com pouca tecnologia e deficiente controle sanitário dos animais. O leite cru apresenta baixa qualidade microbiológica, o que compromete a composição do produto, reduz sua vida de prateleira e pode constituir risco à saúde pública. A qualidade e a segurança dos alimentos estão associadas às boas práticas de produção (BPP). A implantação das BPP resulta na redução do número de microrganismos do leite levando a uma melhor qualidade microbiológica e maior vida de prateleira do produto final. O objetivo deste trabalho foi avaliar o impacto da implantação de boas práticas de ordenha na melhoria da qualidade microbiológica do leite, visando atingir os padrões estabelecidos pela Instrução Normativa 51. Foram aplicadas diferentes práticas de ordenha nos principais pontos de contaminação, identificados previamente, em quatro propriedades do Agreste Pernambucano. As práticas foram avaliadas através da enumeração de microrganismos indicadores aeróbios mesófilos, psicrotróficos, estafilococos coagulase positivos, coliformes totais e Escherichia coli antes e após aplicação das práticas. As práticas adotadas foram: desprezo dos três primeiros jatos de leite, imersão dos tetos em solução clorada, higienização vigorosa e posterior inversão dos latões e baldes para eliminação da água residual. Os resultados demonstram com aplicação das práticas redução média de 99,9% de microrganismos aeróbios mesófilos no leite. As práticas indicadas são simples, eficientes, de fácil incorporação na rotina da ordenha em qualquer situação de tecnificação das propriedades e não requerem gastos com instalações.